(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to know the effect of (swom) strategy on the achievement of social studies subject for first-grade students ,the average and the sample consisted of (79) students from the first –grade students from the first –grade students average in the AI-Zawra secondary school for boys belonging to the Directorate of Education in the second Rusafa in Baghdad. Two groups by (40).student in the experimental group and (39)students in the control group the researcher studied the students of the experimental group using the(swom) strategy and the students of the control group studied the same subject in the usual way . Using the T-test for two independent samples that resulted in the search for the following result there is a statistically. Significant difference between the average scores of students of the experimental group who studied the social subject matter (swom) and the degrees of students of the control group who studied the same subject in the usual way and in favor of the experimental group.